Efficient industrial-current-density acetylene to polymer-grade ethylene via hydrogen-localization transfer over fluorine-modified copper - Bai, Lei; Wang, Yi; Han, Zheng; Bai, Jinbo; Leng, Kunyue; Zheng, Lirong; Qu, Yunteng; Wu, Yuen (Nature communications, 2023)
Electrocatalytic acetylene semi-hydrogenation to ethylene powered by renewable electricity represents a sustainable pathway, but the inadequate current density and single-pass yield greatly impedes the production efficiency and industrial application. Herein, we develop a F-modified Cu catalyst that shows an industrial partial current density up to 0.76 A cm −2 with an ethylene Faradic efficiency surpass 90%, and the maximum single-pass yield reaches a notable 78.5%. Furthermore, the Cu-F showcase the capability to directly convert acetylene into polymer-grade ethylene in a tandem flow cell, almost no acetylene residual in the production. Combined characterizations and calculations reveal that the Cu δ+ (near fluorine) enhances the water dissociation, and the generated active hydrogen are immediately transferred to Cu 0 (away from fluorine) and react with the locally adsorbed acetylene. Therefore, the hydrogen evolution reaction is surpassed and the overall acetylene semi-hydrogenation performance is boosted. Our findings provide new opportunity towards rational design of catalysts for large-scale electrosynthesis of ethylene and other important industrial raw. Efficient electroreduction of acetylene to ethylene is crucial for industrial applications. Here, the authors reported fluorine modified copper for direct conversion of acetylene to polymer-grade ethylene in one single-pass with industrial-current-density.